Forensic Odontoiogy as one of identification methods for unknown victim body - Sara Afari Gadro, Sara Afari Gadro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Various etiologies, especially those are severe in quality, can result in an unidentified victim. In certain conditions, such as in a severe combusted, destructed or fragmented victim, or a skleton as the remmant of a victim forensic odontology has a very essentil role. The teeth are suitable identification materials due to their extreme individual characteristics and their resistance againts many destructing agents. The most important characteristics of the teeth to be used in forensic odontology are among others the anatomical structure, the occlusion, the eruption, the morphology, wear and tear. Antemortem data of the victims teeth is imperative in applicating forensic odontology for victim identification at individual level. If no antemortem teeth data is available, postmortem reconstruction may direct the investigation eventhough not up to individual level. The establishment of dental record is, therefore, very important for people who have life threatehing risk.Key words : teeth - forensic odontology - unknown victim body - identification method - dental record